Davelopment of a Multimedia Website as a Learning Tool for English and Mandarin for Student at PT. Global Mitra Akademi (Oaklearn Center) - Calista Rianty; Hardiansyah Putra; Ricky Ramadhan Harahap (Bahasa Indonesia, 2026)
The use of information technology in education is a solution to improve the effectiveness of learning, especially foreign language learning. At PT. Global Mitra Akademi (Oaklearn Center), English and Mandarin language learning still requires more interactive and easily accessible media. This research aims to develop and implement a multimedia website as a learning tool for English and Mandarin for students at PT. Global Mitra Akademi (Oaklearn Center). The problem in this study includes the process of developing and implementing a multimedia website to support learning activities. The system development method used is the waterfall method. Data collection was carried out through observation, literature study, and interviews with staff and students at PT. Global Mitra Akademi (Oaklearn Center). The research results show a positive response; this e-learning website can facilitate access to materials and support English and Mandarin language learning more effectively.